Web application for secure file transfer - Horký, Vít; Caha, Tomáš (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2025)
This paper focuses on the design and implementation of a web application capable of securely transferring files over the Internet. It aims to be an open-source solution for handling more complex tasks that are underserved by tools freely available on the internet. The application prioritizes ease of use by incorporating integration with Microsoft Single Sign-on (SSO) and provides easy future extensibility for use with multiple storage providers by abstracting its storage layer.
Keywords: file transfer; web application; SSO; .NET; Blazor